Adaptive Schemes for Differentiated Availability-Aware Connection Provisioning in Optical Transport Networks - Kantarci, Burak; Mouftah, Hussein T.; Oktug, Sema F. (Institute of Electrical and Electronics Engineers (IEEE), 2009)
In this paper, we present two adaptive schemes, namely, global differentiated availability-aware provisioning (G-DAP) and link-by-link differentiated availability-aware provisioning (LBL-DAP) for connection provisioning in optical transport networks under dual failure assumption. G-DAP attempts to determine a feasible sharing degree for each availability class for the links in the network globally. As an enhancement to G-DAP, LBL-DAP tries to determine a feasible sharing degree per availability class on each link. Connections belong to one of the five availability classes with the availability requirements of 0.98, 0.99, 0.999, 0.9999, and 0.99999, which are specified in their service level agreement (SLA). We compare the performance of the proposed schemes with a conventional service provisioning scheme, compute a feasible solution (CAFES) under the NSFNET and European optical network (EON) topologies. The simulation results show that the proposed schemes introduce better availability per connection and lower blocking probabilities. LBL-DAP performs the best by monitoring the shareability status of each link periodically with respect to the metrics studied, and decreases resource overbuild.